Midwives Motivation and the Use of Partograph - Kusumawati, Erna; Cahyati, Widya Hary; Rosadah, Shalma (Journal of Creativity Student, 2025)
Background: Maternal Mortality Rate (MMR) is one of the indicators used to assess public health status. In 2023, the highest number of maternal deaths occurred during labor, accounting for 38.94%, highlighting the need for proper management through the use of a partograph as a monitoring tool during childbirth. However, there are challenges in its usage, one of which is the motivation of midwives. Purpose: This study aims to determine the relationship between midwives' motivation and the use of partograph at Fajar Bulan Community Health Center, West Lampung Regency. Method: This study employed a quantitative descriptive research design with a cross-sectional approach. The sampling technique used was Total Sampling, involving 67 midwives. Bivariate analysis was conducted using Spearman’s rank correlation test. Result: The obtained p-value is 0.00 < α (0.05), indicating a significant relationship between midwives' motivation and the use of partographs. Additionally, the correlation coefficient is 0.474, which signifies a moderate or sufficient relationship in a positive direction. This means that the higher the midwives' motivation, the higher the use of partographs at Fajar Bulan Community Health Center, West Lampung Regency. Conclusion: Midwives' motivation is a factor related to the use of partograph at Fajar Bulan Community Health Center, West Lampung Regency. It is recommended to improve services related to the use of partograph as a monitoring tool during labor.